An efficient copper-catalyzed synthesis of symmetrical bis(N-arylbenzamide) selenides and their conversion to hypervalent spirodiazaselenuranes and hydroxy congeners. Issue 21 (12th February 2019) - Kadu, Rahul; Batabyal, Monojit; Kadyan, Heena; Koner, Apurba Lal; Kumar, Sangit
Abstract : A copper catalyzed efficient synthetic method has been developed to access bis( N -arylbenzamide) selenides from 2-halo- N -arylbenzamide substrates and disodium selenide in HMPA at 110 °C. Abstract : A copper catalyzed efficient synthetic method has been developed to access bis( N -arylbenzamide) selenides from 2-halo- N -arylbenzamide substrates and disodium selenide in HMPA at 110 °C. The developed protocol tolerates substituents in both N -aryl and benzamide rings of the 2-halobenzamide substrates and provides an array of bis( N -arylbenzamide) selenides in practical yields. The resulting selenides were transformed into hypervalent spirodiazaselenuranes by oxidation using aqueous hydrogen peroxide. ( N -(1-Naphthyl)) spirodiazaselenurane is also structurally characterized by a single crystal X-ray study. Hydroxy-substituted spiroselenuranes have been prepared by careful demethylation of methoxy-substituted selenides followed by oxidation by hydrogen peroxide. Antioxidant properties for the decomposition of hydrogen peroxide and for the deactivation of radicals of hydroxy-substituted spiroselenuranes have been studied by the thiol assay and 2, 2-diphenyl-1-picrylhydrazyl (DPPH) assay. Both hydroxy-substituted spiroselenuranes exhibit dual mimic functions of glutathione peroxidase (GPx) selenoenzyme and α-tocopherol for decomposition of hydrogen peroxide and deactivation of radicals, respectively.